2007
DOI: 10.1002/art.22898
|View full text |Cite
|
Sign up to set email alerts
|

Effectively measuring adherence to medications for systemic lupus erythematosus in a clinical setting

Abstract: Objective. To assess the reliability and concurrent validity of the Medication Adherence Self-report Inventory (MASRI) when used in systemic lupus erythematosus (SLE), to investigate the predictive validity of the MASRI using pharmacy refill information as the criterion standard, and to propose a sensible approach to the screening for nonadherence in a clinical setting. Methods. Adherence to 2 medications (hydroxychloroquine and prednisone) was measured in 55 patients using the MASRI, pill counts, and physicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 18 publications
4
83
2
Order By: Relevance
“…Thus, the group led by Koneru, 2008 found adherence to the general medication of 80%, when to GCS was 61%, much lower than adherence to GCS among the patients included in our study, who demonstrated adherence to GCS of 92.85% [11]. We also compared HCQ compliance in our patients who showed the adherence of 92.15% versus 49% in the study conducted by Koneru.…”
Section: Discussionmentioning
confidence: 60%
“…Thus, the group led by Koneru, 2008 found adherence to the general medication of 80%, when to GCS was 61%, much lower than adherence to GCS among the patients included in our study, who demonstrated adherence to GCS of 92.85% [11]. We also compared HCQ compliance in our patients who showed the adherence of 92.15% versus 49% in the study conducted by Koneru.…”
Section: Discussionmentioning
confidence: 60%
“…Kimmel et al 12 reported that in a 32-week study analyzing 136 patients taking warfarin, 92% of patients had at least 1 inappropriate medication administration time and that 36% took their medication incorrectly at least 20% of the time. Koneru et al 13 found that among 50 patients with lupus, more than 50% of those studied were not adherent to their medications. In an analysis of 23 patients positive for human immunodeficiency virus, although 95% of the patients stated that their medications were life-prolonging, the rate of proper medication adherence was between 66% and 78%.…”
Section: Discussionmentioning
confidence: 99%
“…Part A of the MASRI is 87% sensitive and 86% specific for identifying patients who were nonadherent (21). Part A consists of five 4-point scale items and one visual analog scale (VAS) item.…”
Section: Methodsmentioning
confidence: 99%